A Reference Architecture For Digital Preservation - Antunes, G. J. (2010)
Apart from being a technological issue, digital preservation raises several organizational challenges. These challenges are starting to be addressed in the industrial design and e-Science domains, where emerging requirements cannot be addressed directly by OAIS. Thus, new approaches to design and assess digital preservation environments are required. We propose a Reference Architecture as a tool that can capture the essence of those emerging preservation environments and provide ways of developing and deploying preservation-enabled systems in organizations. This paper presents the main concepts from which a Reference Architecture for digital preservation can be built, along with an analysis of the environment surrounding a digital preservation system. We present a concrete Reference Architecture, consisting of a process to derive concrete digital preservation architectures, which is supported by an architecture framework for organizing architecture descriptions. In that way, organizations can be better prepared to cope with the present and future challenges of digital preservation.